Synthesis and in vivo evaluation of 11C‐labeled (1, 7‐dicarba‐closo‐dodecaboran‐1‐yl)‐N‐[(2S)‐1‐ethylpyrrolidin‐2‐yl]methylamide†. (5th December 2013) - Gómez‐Vallejo, Vanessa; Vázquez, Naiara; Gona, Kiran Babu; Puigivila, Maria; González, Mikel; Sebastián, Eneko San; Martin, Abraham; Llop, Jordi; Dilworth, Jonathan R.; Pascu, Sofia I.
<x xml:space="preserve">Abstract</x> Boron clusters, and especially dicarba‐closo‐dodecaboranes, can be used as hydrophobic pharmacophores in the design of new drugs and radiotracers because of their hydrophobic character, spherical structure, and excellent chemical and photochemical stability. In the present paper, the synthesis and in vivo evaluation of 11C‐labeled (1, 7‐dicarba‐closo‐dodecaboran‐1‐yl)‐N‐[(2S)‐1‐ethylpyrrolidin‐2‐yl]methylamide, an analog of the D2 receptor ligand [11C]raclopride, is described. The radiosynthesis was approached by reaction of the demethylated precursor with [11C]CH3I in basic media; moderate radiochemical yields (18.2 ± 2.8%, decay corrected), and excellent radiochemical purities (>98%) were obtained in overall synthesis time of 50 min. In vivo assays showed a biodistribution pattern with significant uptake in liver, kidneys and lungs at short times (t = 4 min) after administration and increasing accumulation in bladder at longer times (t ≥ 14.5 min). Although brain positron emission tomography scans showed good blood brain barrier penetration, the high unspecific uptake observed in different brain regions impedes its applicability as D2 receptor ligand. Copyright © 2013 John Wiley & Sons, Ltd.